Harnessing AI-assisted Writing in Educational Institutions: A Systematic Literature Review - Sudirman, Anselmus; Kristanto, TMA; Vitalya Gemilang, Adria; Rais, Burhanudin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This review aims to explore AI-assisted writing tools that can meet diverse learning needs and improve student writing performance in educational settings. It also examines the strategies teachers utilize to effectively integrate these tools into academic environments, ensuring student engagement and maintaining academic standards within educational institutions. Method: The analysis utilized the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology, which involved a systematic synthesis of findings from 22 selected articles gathered from a total of 1500 scholarly sources published in journals indexed by Scopus and Web of Science (2020-2025). These sources were accessed through various databases, including Web of Science, Scopus, PubMed, ScienceDirect, SpringerLink, Tandfonline, and IEEE Explore. Results: The findings indicate that AI writing tools enhance grammatical accuracy, structural clarity, and syntactic sophistication, providing timely and thorough feedback that complements traditional teaching methods. They play an essential role in fostering creativity and engagement by facilitating brainstorming and the structuring of ideas. The ethical use of AI and its effects on academic integrity were recognized as crucial considerations for teachers. The implications highlight the necessity of developing integrated feedback models that combine AI and human input, establishing clear ethical standards, and improving critical AI literacy among students. Novelty: The study highlights the transformative possibilities of AI-assisted writing tools in education, promoting their deliberate incorporation to improve conventional teaching methods and enhance students' learning experiences. This review offers an entirely new viewpoint through its thorough examination of AI integration in different educational environments, delivering detailed insights that inform future teaching methods and promote a well-rounded view of technology-enhanced learning.